Pengaruh Kombinasi Pupuk Ab Mix Dengan Poc Azolla Pinnata Terhadap Pertumbuhan Dan Hasil Tanaman Pakcoy (Brassica Rapa L.) Hidroponik Sistem Wick - laura oktafiani; Hayatul Rahmi; Devie Rienzani Supriadi (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the important things in cultivating plants in a hydroponic system is a nutrient solution because the nutrients needed by plants can only be fulfilled by providing a nutrient solution. The aim of this study was to obtain the best combination of AB mixed fertilizer with POC Azolla pinnata for Pakcoy (Brassica rapa L.) hydroponic wick system. The research method used a single factor randomized block design (RBD) consisting of 6 treatments which were repeated 4 times. The treatment combination consisted of A = AB mix (5.25 ml/L), B = AB mix (10.5 ml/L), C = AB mix (0 ml/L) + POC Azolla pinnata (10 ml/L) , D = AB mix (0 ml/L) + POC Azolla pinnata (15 ml/L), E = AB mix (5.25 ml/L) + POC Azolla pinnata (10 ml/L), F = AB mix ( 5.25 ml/L) + POC Azolla pinnata (15 ml/L). The results of the study showed that treatment B (AB mix (10.5 ml/L) produced the highest fresh weight of pakcoy plants in the hydroponic wick system which was 47.56 grams and in treatment E (5.25 ml/L + 10 ml/L) yielded a significant plant height of 20.77 cm.Based on the results of the research conducted, it can be concluded that the administration of a combination of AB mix with POC Azolla pinnata on the wick system hydroponic pakcoy plants showed a significant effect on all growth and yield parameters.